TOURISM REVITALISING PATH AND INNOVATIVE DEVELOPMENT STRATEGIES OF TRADITIONAL CRAFT CULTURAL HERITAGE - Zhang, Yun; Musdi, Shanat (Aliva Global Research and Development, 2021)
The global society has been facing great changes in the past century, and there has been estrangement and even rupture between the traditional arts and cultural heritage and daily life. Therefore, it is necessary to revitalize, maintain, and reproduce the tourism development that driven from the view of nostalgia of traditional craft cultural heritage. This paper draws on the cultural practice of Birmingham School and Johnson and Hall's cultural circuit theory, and integrates the subjective cultural significance and the demands of cultural heritage tourism from the theoretical perspective. In analysing the psychological game relationship among governments, enterprises, inheritors and consumers, and put forward an innovative development strategy that uses data resources to drive and inherit from life to promote the creative transformation of traditional skills and cultural heritage. This study attempts to construct a conceptual model of the revitalising path and innovation strategy of traditional craft cultural heritage tourism. It enriches the theoretical scope of the research on the cultural heritage of traditional craftsmanship and promotes the development of cultural industry.